ECOLOGICAL SAFETY OF THE REGIONS: ACHIEVING THE EU STANDARDS - Yermoshkina, Olena (My University, 2012)
On the basis of comparative analysis of the results of economic, production and environ- mental activity and indexes that testify the quality of life in context of environment of European countries the main trends of maintaining the ecological safety of the regions were defined. The crucial issues should be solved in the framework of providing the high level of ecological safety of the regions in globalization and integration conditions are discovered. The main directions for pre-ins countries in achieving the EU standards of environmental protection were proposed.
ECOLOGICAL SAFETY OF THE REGIONS: ACHIEVING THE EU STANDARDS
On the basis of comparative analysis of the results of economic, production and environ- mental activity and indexes that testify the quality of life in context of environment of European countries the main trends of maintaining the ecological safety of the regions were defined. The crucial issues should be solved in the framework of providing the high level of ecological safety of the regions in globalization and integration conditions are discovered. The main directions for pre-ins countries in achieving the EU standards of environmental protection were proposed.